SIMBOL DAN MAKNA TARI BEDAYA PAKUNGWATI DI KERATON KASEPUHAN CIREBON - Maysarah, - (2018)
SkripsiiniberjudulSimbol Dan MaknaTariBedayaPakungwatiDiKeratonKasepuhan Cirebon,permasalahan yang terdapatpadatariBedayaPakungwatiadalahsimboldanmakna yang terdapatpadagerakdanbusanasertairinganmusik.Tujuanpenelitianuntukmendeskripsikansertamenganalisistentangpermasalahan yang akanditelitiyaitulatarbelakangterciptanyatariBedayaPakungwati, simboldanmaknagerak, simboldanmaknatatarias, busanadaniringantari. sementarametode yang digunakandalampenelitianiniadalahmetodedeskriptifanalisismelaluipendekatankualitatif. HasilpenelitianmenunjukantariBedayaPakungwatidi keratonKasepuhan Cirebon memilikipenanamannilai-nilaiperempuan.Simboldanmakna yang terkandungpadatariBedayaPakungwatimemilikiartisikapseorangperempuan. Tata riasdanbusanaterddpatsimboldanmaknatatacarapakaianseorangperempuan yang lemahlembut. KesimpulandaripenelitianinibahwatariBedayaPakungwatimemilikinilai-nilaiperempuandankepatuhanseorangistriterhadapsuaminya;---This thesis is entitled Symbols and Meanings of BedayaPakungwati Dance in KertatonKasepuhan Cirebon, the problems found in BedayaPakungwati dance are symbols and meanings contained in the movements and clothing and musical accompaniment. The purpose of the research is to describe and analyze the problems to be studied, namely the background of the creation of BedayaPakungwati dance, symbols and meaning of motion, symbols and meanings of makeup, clothing and dance accompaniment. while the method used in this research is descriptive analysis method through a qualitative approach. The results of the study show that BedayaPakungwati dance in the Kasepuhan Cirebon palace has the cultivation of women's values. The symbols and meanings contained in BedayaPakungwati dance have the meaning of a woman's attitude. Makeup and clothing are symbols and meanings of a woman's soft clothing. The conclusion of this study that BedayaPakungwati dance has female values and a wife's adherence to her husband